Thoracic Vertebrae Radiography With Suspected Osteoporosis At Royal Prima Hospital Medan - Tarigan, Liberti; Sidauruk, Juliana Lansiar (Jurnal Ilmu Sosial Mamangan, 2024)
Thoracic vertebrae are bones that form part of the backbone or spine consisting of 12 segments starting from Thoracal 1 to Thoracal 12. Osteoporosis is porous bone that has the characteristic of low or reduced bone mass and decreased bone tissue quality, which can cause bone fragility. This examination uses Antero-Posterior and Lateral projections and shadow recording using Digital Radiography (DR). Using a General X-Ray Unit with a maximum capacity of 500 mA. The type of research used is qualitative and descriptive research. The data collection technique is in the form of observation and interviews. With the results of the study obtained from the Royal Prima Medan Hospital.